Pengaruh Tekanan Anggaran, Ambiguitas Peran, Opportunistic Behaviour, Dan Self Esteem Terhadap Budgetary Slack - Jheny Steffani Steffani Gusti; Efrizal Syofyan (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the influence budgetary pressure, role ambiguity, opportunistic behaviour and self on the Budgetary slack. The population in this studyare all OPD in Bukittinggi as many as 29 OPD. The sample in this study using asampling technique total sampling. The methods use descriptive statistic analysis and multiple linear regression. The results showed that budgetary pressure has no effect onbudgetary slack. Role ambiguity has no effect on budgetary slack. Opportunistic behaviour has no effect on budgetary slack and also self esteem effected on budgetary slack